1956
DOI: 10.1113/jphysiol.1956.sp005441
|View full text |Cite
|
Sign up to set email alerts
|

Secretion by the parotid gland of the sheep

Abstract: Secretion by the parotid gland of the sheep has been studied in acute preparations and by means of fistulae. The sheep is unusual in having a continuous flow of parotid saliva which increases in amount both with feeding and with cud chewing (Ellenberger & Hofmeister, 1887). As in the ox its parasympathetic nerve supply arrives via the buccal branch of the mandibular nerve as fine branches which go from the anterior border of the masseter muscle with the duct to the gland (Moussu, 1888(Moussu, , 1890, not via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
58
0

Year Published

1957
1957
1993
1993

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 6 publications
6
58
0
Order By: Relevance
“…If, however, the sheep were taken out of its cage and gently secured on its side, the blood pressure rose to 100-130 mm Hg and in sheep P.F. 7, as in other sheep tested, this procedure inhibited the continuous secretion of parotid saliva characteristic of the ruminant, as also did continued stimulation of the cervical sympathetic in anaesthetized sheep (Coats et al 1956). Occlusion of the right (innervated) carotid loop for 3-10 min raised the blood pressure by 10-50 mm Hg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If, however, the sheep were taken out of its cage and gently secured on its side, the blood pressure rose to 100-130 mm Hg and in sheep P.F. 7, as in other sheep tested, this procedure inhibited the continuous secretion of parotid saliva characteristic of the ruminant, as also did continued stimulation of the cervical sympathetic in anaesthetized sheep (Coats et al 1956). Occlusion of the right (innervated) carotid loop for 3-10 min raised the blood pressure by 10-50 mm Hg.…”
Section: Resultsmentioning
confidence: 99%
“…16 the left superior cervical ganglion and a portion of the left cervical sympathetic trunk in the root of the neck were removed, and the left occipital arteryligated. The removal of the ganglion was confirmed histologically, and it was demonstrated at operation that stimulation of the cranial end of the divided sympathetic trunk did not cause the characteristic gush of parotid saliva (Coats, Denton, Goding & Wright, 1956). …”
Section: Methodsmentioning
confidence: 99%
“…Care was taken that the saliva specimen was not contaminated with preformed saliva within the duct cannula, but it was certainly a mixture of saliva secreted during stimulation and preformed saliva within the intraglandular duct system. There was no method of accurately assessing the capacity of the intraglandular duct system, but cervical sympathetic stimulation (Coats et al 1956) indicated that the saliva specimen obtained was shows that the concentration changes were roughly reciprocal, but that the fluctuations in sodium concentration occurred at approximately twice the rate of the potassium fluctuations. The different time relationship is better illustrated in Fig.…”
Section: Salivary Flow Following Motor Nerve Stimulationmentioning
confidence: 99%
“…Cannulation of the parotid duct, and the preparation of the parasympathetic nerve (Moussu'# nerve) for stimulation have been previously described (Coats, Denton, Goding & Wright, 1956 (Denton, 1956).…”
mentioning
confidence: 99%
“…A large fraction of this saliva is supplied by the parotid glands, which have been studied by many workers (Colin, 1886;Scheunert & Trautmann, 1921;Coats, Denton, Goding & Wright, 1956;Denton, 1957b;Kay, 1958). The parotid glands secrete rapidly and continuously, but the submaxillary glands secrete little except during feeding periods (Colin, 1886;Scheunert & Trautmann, 1921).…”
mentioning
confidence: 99%